What we have learnt (so far) about deliberative dialogue for evidence-based policymaking in West Africa - (:unkn) unknown (My University, 2017)
Policy decisions do not always take into account research results, and there is still little research being conducted on interventions that promote their use, particularly in Africa. To promote the use of research evidence in Africa, deliberative dialogue workshops are increasingly recommended as a means to establish evidence-informed dialogue among multiple stakeholders engaged in policy decision-making. In this paper, we reflect on our experiences of conducting national workshops in six African countries, and we propose operational recommendations for those wishing to organise deliberative dialogue. Our reflective and cross-sectional analysis of six national deliberative dialogue workshops in which we participated shows there are many specific challenges that should be taken into account when organising such encounters. In conclusion, we offer operational recommendations, drawn from our experience, to guide the preparation and conduct of deliberative workshops.
Keywords: African Research